Welcome to the terror-go-round - Cascone, A. G. (Mahwah, NJ : Troll, 1997)
A ride on the merry-go-round spins Alex and Joey into a carnival of terrors...
Keywords: Carnivals -- Juvenile fiction; Horror tales